Au-delà du sensible: espaces et dépositions - Viana, Joaquim (Verbum – Analecta Neolatina, 2014)
If there is evidence of a radical change of direction in the understanding of space, there is also, on the other hand, a conservative tendency for training and playing a dimensional space and above codified identical reproductions and easy recognition. In principle, this codified space is connected to the possibility of creating a sensitive axiomatic field (formerly: significant field and ghostly field) capable of imparting a new orthodoxy, a new value system to form/build a consistent image world.